Association of Health-Related Quality of Life with Atherosclerotic Cardiovascular Disease: Lifetime Risk Pooling Project - Hongyan Ning; Kiarri N. Kershaw; Norrina Bai Allen; John Wilkins; Donald M Lloyd-Jones (Elsevier, 2021)
Objective: The Pooled Cohort Equations (PCE) serve as the platform for quantitative risk assessment for atherosclerotic cardiovascular disease (ASCVD). Data are sparse regarding the benefit of adding health-related quality of life (HRQoL) measures to the PCE. We sought to estimate the association of HRQoL with ASCVD events and evaluate the potential utility of adding HRQoL to the PCE in refining quantitative risk assessment for primary prevention decisions. Methods: Three multi-ethnic longitudinal cohorts were included in the study. HRQoL was measured using the SF-12 physical component summary (PCS) and mental component summary (MCS); higher PCS or MCS scores indicate better HRQoL. We constructed a four-level HRQoL status variable: MCS <50 and PCS <50; MCS <50 and PCS ≥50; MCS ≥50 and PCS <50; MCS ≥50 and PCS ≥50. Harrell's C statistics and net reclassification improvement (NRI) analyses were used to assess the added predictive ability of HRQoL for incident ASCVD. Results: A total of 9,904 individuals were included in the analysis, of whom 4,743 were in the low risk subgroup (<5% predicted 10-year risk). HRQoL status, PCS and its subscale scores were independent predictors of ASCVD events. HRQoL improved both discrimination (delta C: 0.004, p = 0.05) and reclassification (cNRI: 0.15, p<0.01) modestly when added to PCE; 3% and 6% of individuals with events were correctly reclassified to higher risk in the overall sample and low risk subgroup, respectively. Conclusion: HRQoL is an independent predictor of ASCVD events, and improves ASCVD risk prediction significantly, though modestly, overall and in low-risk individuals. HRQoL may be a cost-effective risk-enhancing factor for refining quantitative risk assessment for primary prevention decisions.